Prevalence and Clinical Impact of Concomitant Mutations in Anaplastic Lymphoma Kinase Rearrangement Advanced Non-small-Cell Lung Cancer (Guangdong Association of Thoracic Oncology Study 1055) - Li, Meichen; Hou, Xue; Zhou, Chengzhi; Feng, Weineng; Jiang, Guanming; Long, Hao; Yang, Shuang; Chen, Jing; Wang, Na; Wang, Kaicheng; Chen, Likun (Frontiers in Oncology, 2020)
Background: In patients with anaplastic lymphoma kinase (ALK) rearrangement-positive advanced non-small-cell lung cancer (NSCLC), ALK inhibitors are now the standard treatment, but their clinical efficacy varies widely for each patient. In this multicenter retrospective study, we evaluated the clinical efficacy of crizotinib according to the ALK rearrangement variants and concomitant mutations present. Patients and Methods: A total 132 patients with ALK rearrangement advanced NSCLC from 4 centers in Guangdong province, China were evaluated. All patients received crizotinib treatment and their ALK rearrangement status was identified by next-generation sequencing (NGS). Results: The median progression-free survival (PFS) in patients with EML4-ALK rearrangement (n = 121), non-EML4-ALK rearrangement (n = 5), and EML4-ALK arrangement accompanied by non-EML4-ALK rearrangement (n = 6) was 12.8 months, 7.5 months, and 7.4 months, respectively, with no significant difference between them (p = 0.1554). Similarly, among patients with various EML4-ALK variants (variant 1, variant 3a/b, and other variants), the median PFS values were again comparable. According to baseline NGS data, the median PFS in patients who had ALK rearrangement only, ALK rearrangement and concomitant tumor-suppressor gene mutations, and ALK rearrangement and concomitant oncogene mutations was 14.2 months, 10.9 months, and 4.9 months, respectively; p = 0.0002). A multivariable analysis indicated that concomitant oncogene mutations and tumor-suppressor gene mutations were both negative factors influencing the efficacy of crizotinib in ALK rearrangement NSCLC. Conclusion: Concomitant oncogene mutations and tumor-suppressor gene mutations had negative effects on the efficacy of crizotinib, while various ALK variants had a similar influence.